Investigation on the relationship between renal NONO expression, fibrosis and prognosis in diabetic nephropathy - Yang, Shuang; Liao, Huiyuan; Ding, Hanlu; Xu, Xingli (Frontiers in Endocrinology, 2025)
BackgroundRenal interstitial fibrosis (RIF) is an important manifestation of Diabetic nephropathy (DN) progression. Non-POU domain containing octamer-binding protein (NONO) is crucial in fibrosis in cardiovascular diseases, but its role in DN fibrosis remains unclear. This study explores the expression of NONO in DN and its correlation with Matrix Metalloproteinase-9 (MMP-9, as an important regulator of fibrosis), renal fibrosis, and prognosis.MethodsForty patients with type 2 diabetes mellitus (T2DM) with pathologically confirmed DN were included, divided into early DN group (n=20) and late DN group (n=20). 6 normal renal tissue as control group. HE, Masson staining, immunohistochemical staining and Immunofluorescence double staining were performed. The correlation between NONO expression levels and MMP-9 as well as clinical pathological data was analyzed. Cox regression analysis and Kaplan-Meier survival curves were used to evaluate the relationship between renal tissue NONO expression levels and DN prognosis.ResultsCompared with control group, NONO expression levels in renal tissues of DN patient were increased, and the late DN group was higher than the early DN group (P<0.05). NONO and MMP-9 expression were positively correlated with multiple clinical and Fibrosis-related pathological indicators, and NONO expression was positively correlated with MMP-9(P<0.05). Patients with high renal NONO expression had lower kidney progression-free survival rates.ConclusionsNONO expression levels correlate positively with MMP-9, collagen and renal damage indicators in renal tissues of DN patients. High NONO expression is linked to poor renal prognosis in DN. NONO may contribute to renal tissue fibrosis in DN by regulating MMP-9 levels.